Characterization of Enterococcus faecalis JF85 and Enterococcus faecium Y83 isolated from Tibetan yak (Bos grunniens) for ensiling Pennisetum sinese. (June 2018) - Li, Junfeng; Yuan, Xianjun; Desta, Seare T.; Dong, Zhihao; Mugabe, Wazha; Shao, Tao
Highlights: Two bacteria (JF85 and Y83) with higher CMCase and FPase activities were isolated from Tibetan yak. Application of the two isolates improved fermentation quality of P. sinese silages. Isolates could accelerate the degradation of structural carbohydrates during ensiling. P. sinese ensiled with the isolates enhanced enzymatic hydrolysis efficiency. Abstract: Two bacteria strains with cellulolytic potential isolated from Tibetan yak ( Bos grunniens ) rumen were identified as Enterococcus faecalis (JF85) and Enterococcus faecium ( Y83). Isolates grow well within a range of temperature 15 to 55 °C and pH 3.0–7.0, respectively. Two strains were inoculated with or without Lactobacillus plantarum (Lp) to Pennisetum sinese silage for 90 days. All inoculants increased lactic acid content, decreased pH and lignocellulose contents compared with silage without additives (control). The lowest pH, highest lactic acid and largest reduction in lignocellulose contents were observed in JF85+Lp and Y83+Lp silages. Isolates alone or in combination with Lp significantly increased WSC, mono- and disaccharides contents as compared to the control. Combined addition efficiently improved enzymatic hydrolysis of Pennisetum sinese silage, indicated by higher glucose yield and cellulose convertibility. Pennisetum sinese ensiled with combined additives is a suitable storage and pretreatment method prior to sugars production from energy crop.